Realizing Impure Functions in Interaction Nets - Jiresch, Eugen (Electronic Communications of the EASST, 2011)
We propose and illustrate first steps towards an extension of interaction nets based on monads to handle functions with side effects (e.g., I/O, exceptions). We define three monads for common types of side effects and show their correctness by proving the monad laws.